Comparison of Patient Demographics and Utilization Trends of Robotic-Assisted and Non-Robotic-Assisted Unicompartmental Knee Arthroplasty - Vakharia, Rushabh M.; Sodhi, Nipun; Cohen-Levy, Wayne B.; Vakharia, Ajit M.; Mont, Michael A.; Roche, Martin W. (The Journal of Knee Surgery, 2019)
Robotic-assisted unicompartmental knee arthroplasty (RAUKA) is an emerging area of interest. The purpose of this study was to compare (1) different patient demographic profiles; (2) annual primary and revision utilization rates; (3) risk factors for revision procedures; and (4) survivorship between RAUKA and manual UKA (MUKA). Using the PearlDiver database, patients who underwent RAUKA or MUKA between 2005 and 2014 within the Medicare database were identified, yielding a total of 35,061 patients (RAUKA = 13,617; manual = 21,444). Patient demographics (age, gender, comorbidities, Charlson-Comorbidity Index, and geographic region) were compared between cohorts. Annual primary and revision utilization rates as well as risk factors for revision procedures were also compared. Kaplan–Meier survivorship was also calculated. The Pearson χ2 test was used to test for significance in patient demographics, whereas the Welch t-test was used to compare the incidence of revisions as well as the revision burden (proportion of revisions to total sum of primary and revision procedures). Multivariate binomial logistic regression analysis was performed to compare risk factors for revision procedures. There were statistically significant differences in RAUKA versus MUKA patients with respect to age (p < 0.001), gender (p < 0.001), and region (p < 0.001). RAUKA procedures performed increased over 12-fold compared with manual, which increased only 4.5-fold. RAUKA procedures had significantly lower revision incidence (0.99 vs. 4.24%, p = 0.003) and revision burden (0.91 vs. 4.23%, p = 0.005) compared with manuals. For patients undergoing RAUKA, normal (19–24 kg/m2) and obese (30–39 kg/m2) body mass index (p < 0.05), congestive heart failure (p = 0.004), hypothyroidism (p < 0.001), opioid dependency (p = 0.002), and rheumatoid arthritis (p < 0.001) were risk factors for a revision procedure. Kaplan–Meier survival curve 3 years following the index procedure to all-cause revisions demonstrated that RAUKA patients maintained nearly 100% survivorship compared with manual patients who had 97.5% survivorship. The data demonstrate increased utilization of RAUKA in the United States. The current data indicated that RAUKA has significantly lower revision rates and improved survivorship compared with patients undergoing non-RAUKA within Medicare patients.
Keywords: unicompartmental knee arthroplasty; robotic-assisted; Medicare; trends; revision